Wide-angle quad-band polarisationinsensitive metamaterial absorber - Agarwal M.; Behera A.K.; Meshram M.K. (My University, 2025)
Closed ring resonator (CRR)-based quad-band metamaterial absorber is presented. The unit cell of proposed absorber consists of four separate CRRs which are diagonally connected to square patches enclosed within an individual CRR. The structure is fabricated on 0.8 mmthick FR4 substrate. Simulated peak absorptivities of 98.5, 97.7, 94.8, and 96% are obtained at 4.34, 6.68, 8.58, and 10.64 GHz, respectively. The measured and simulated absorption characteristics of the proposed absorber are in good agreement. The proposed absorber is wide angle and polarisation insensitive and has identical absorption characteristics for both transverse-electric and transverse-magnetic polarised radiations. © The Institution of Engineering and Technology 2016.